IMPROVING STUDENTS LEARNING OUTCOME OF ENGLISH BY USING ROLE PLAYING AT SDN 022 RUMBIO - Wida Rianti (Journal of English Language and Education, 2017)
The aim of this research is to describe the application of role playing to improve the learning outcomes of students class V SDN 022 Rumbio. The formulation of the problem in this research is how the application of role playing to improve learning outcomes of English by using role playing students at V grade of SDN 022 Rumbio. This research was conducted in class 002 Rumbio. This research was conducted in two cycles and each cycle was held twice. The subject of this research is the students of class V 002 Pulau SarakKampar district which amounted to 27 people, with the number of male students 13 people, and female students 14 people. The techniques of collection Data used in this research are of observation, documentation, and evaluation. Based on the research results can be concluded that in the first cycle is still quite good with an average of 70.25, then from 27 students only 19 students or 70.37% who achieve mastery individually. Students' learning outcomes in cycle II is quite good with an average of 87.29, and 25 students complete or 92.59% who achieve mastery individually. Thus it can be concluded that with the implementation of role playing model can improve the learning outcomes of English on the students at Vgrade of SDN 002 Rombio